2005
DOI: 10.2202/1540-8884.1076
|View full text |Cite
|
Sign up to set email alerts
|

Why Can't We All Just Get Along? The Reality of a Polarized America

Abstract: According to Morris Fiorina, Americans are moderate, tolerant, and ambivalent in their political attitudes. This has always been true and it is, if anything, more true today than in the past. The culture war is almost entirely an elite phenomenon, driven by a small group of activists on the left and right who exert influence far out of proportion to their numbers. It is the elites and activists who are polarized, not the public. In this study we use data from the American National Election Studies and nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
130
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(137 citation statements)
references
References 6 publications
5
130
0
2
Order By: Relevance
“…Fiorina et al (2005) and Fischer and Hout (2006) reach more or less the same conclu-sions. In contrast, Abramowitz and Saunders (2005) suggest that the mass public is deeply divided between red states and blue states and between churchgoers and secular voters.…”
Section: Public Opinion Polarizationmentioning
confidence: 93%
See 3 more Smart Citations
“…Fiorina et al (2005) and Fischer and Hout (2006) reach more or less the same conclu-sions. In contrast, Abramowitz and Saunders (2005) suggest that the mass public is deeply divided between red states and blue states and between churchgoers and secular voters.…”
Section: Public Opinion Polarizationmentioning
confidence: 93%
“…In this case, there is clear evidence of polarization between self-identified liberals and conservatives, as well as among party affiliates and political activists (DiMaggio et al 1996;Abramowitz and Saunders 2005;Fiorina et al 2005). Bafumi and Shapiro (2007), analyzing the trend in the mean position of Democrats and Republicans and liberals and conservatives with respect to a large set of political issues, have found that partisans and ideologues are increasingly divided not only on issues such as abortion, gay rights, and the role of religion, but also on issues of race and civil rights.…”
Section: Public Opinion Polarizationmentioning
confidence: 97%
See 2 more Smart Citations
“…5 But a large slice of the most active voters are polarised. 6 This confusion highlights the importance of understanding the size and organization of political parties.…”
Section: Formal Parties and Political Networkmentioning
confidence: 99%